Discovering utility between the descriptive and the normative - Patrik Kjærsdam Telléus (Akademisk Kvarter, 2016)
In the article the moral notion of utility is examined. By reading John Stuart Mill’s Utilitarianism the paper argues that moral concepts, like the application of utility, incorporates both normative and descriptive elements, i.e. it is both abstract and factual in nature. Therefore the paper claims that facts are a vital part of moral behavior; and that descriptive elements are essential for normative judgment and moral reasoning. The paper supports its claim by showing that the moral conceptualization of utility includes the incorporation of facts, and that the density, or quality of that incorporation is equivalent to the certainty and comfort by which the conceptualization is articulated.